Integration of Tumbaga Holing as a Legal Framework: Realizing Justice and Harmony in The Mandailing Traditional Society - Lubis, Ikhsan; Siregar, Taufik; Lubis, Duma Indah Sari; Lubis, Andi Hakim (PERADA, 2024)
This study explores the integration of local values, particularly the Tumbaga Holing customary law, into Indonesia's national legal framework. Tumbaga Holing, as the customary legal system of the Mandailing community, plays a crucial role in regulating social life and maintaining communal harmony. However, the process of integrating it into positive law faces various challenges, ranging from differences in legal paradigms to the marginalization of communal rights (ulayat). This research adopts a normative juridical approach, analyzing specific articles within the Basic Agrarian Law (UUPA) and regulations related to indigenous communities. The results show that Tumbaga Holing has the potential to contribute to the national legal system, particularly in the areas of natural resource management and dispute resolution. However, challenges such as lack of formal recognition, legal bureaucracy, and political-economic power imbalances hinder this integration. Proposed solutions include strengthening indigenous institutions, promoting customary law awareness, and revising regulations to be more inclusive of indigenous communities. These efforts are expected to ensure that local values ??are fairly accommodated within the national legal framework.